Application of ozone therapy as an alternative treatment in Malaysia according to islamic perspective - Safiai M.H.; Kashim M.I.A.M.; Mat Isa F.N.; Yusoff A.F.; Jamsari E.A.; Zin D.M.M. (IAEME Publication, 2024)
Indexed by Scopus